Mean platelet volume predicts the glycemic control deterioration in diabetes mellitus type 2 patients - Damira Kadić; Sabaheta Hasić; Emina Spahić (Medicinski glasnik, 2016)
Aim: To investigate association of mean platelet volume (MPV) and glycemic control markers, and whether MPV could be used as a predictor of deterioration of glucoregulation in Diabetes mellitus type 2 (DMT2) patients. Methods: The cross-sectional study included 106 DMT2 patients, treated at the Primary Health Care Centre in Zenica, distributed into groups according to glycated haemoglobin (HbA1c) values: A (n=44, HbA1c ?7.0%) and B (n=62, HbA1c>7.0%). Spearman’s correlation coefficients were calculated to evaluate the relationships between MPV and glycemic control markers. Binomial logistic regression analysis was performed to estimate the relationship between glycemic control, as dichotomous outcome, and MPV as the main predictor. Diagnostic value of MPV as a marker for poor glucoregulation was estimated by using ROC analysis. Results: Mean platelet volume was significantly higher in the group B compared to the group A (p<0.0005). Significant positive correlations of MPV with fasting blood glucose and HbA1c were found in the total sample (rho=0.382, p<0.0005; rho=0.430, p<0.0005, respectively). Mean platelet volume was positively associated with the risk of inadequate glycemic control, with 2 times increased odds of inadequate glycemic control per femtoliter greater MPV (Exp (?) =2.195; 95% CI=1.468 - 3.282, p<0.0005). The area under ROC curve for MPV was 0.726 (95% CI: =0.628-0.823, p <0.0005). At the best cut-off value 9.55 fL, MPV showed sensitivity of 82% and specificity of 54.5%. Conclusion: Mean platelet volume correlates with glycemic control markers in DMT2 patients. It could be used as a simple and cost-effective predictor of deterioration of glucoregulation.
Keywords: platelet activation; hemoglobin A; glycosylated; logistic models; risk assessment; ROC curve